Mangiterpenes A–C and 2′, 3′-seco-manginoid C, four sesquiterpene/monoterpene–shikimate–conjugated spirocyclic meroterpenoids from Guignardia mangiferae. (August 2019) - Chen, Keliang; Chen, Chunmei; Guo, Jieru; Sun, Weiguang; Liu, Junjun; Yang, Jing; Liu, Xiulan; Wang, Jianping; Luo, Zengwei; Zhu, Hucheng; Zhang, Yonghui
Abstract: Mangiterpenes A–C and 2′, 3′- seco -manginoid C, four undescribed sesquiterpene/monoterpene–shikimate–conjugated meroterpenoids with spiro ring systems, were isolated from Guignardia mangiferae . The structures and absolute configurations of these compounds were established by comprehensive spectroscopic analyses and electronic circular dichroism (ECD) calculations. Mangiterpenes A–C represent the first examples of sesquiterpene–shikimate-conjugated spirocyclic meroterpenoids, and 2′, 3′- seco -manginoid C features an unexpected 2′, 3′- seco -manginoids skeleton. Mangiterpene C strongly inhibited the production of NO inducted by LPS, with an IC50 value of 5.97  μ M. It showed an anti-inflammatory effect by means of blocking in the NF-κB signaling pathway and decreasing the expression of inflammatory mediators. Graphical abstract: Four undescribed sesquiterpene/monoterpene–shikimate–conjugated meroterpenoids with spiro ring systems were isolated from Guignardia mangiferae . Image 1 Highlights: Four undescribed meroterpenoids were isolated from Guignardia mangiferae. Mangiterpenes A–C are sesquiterpene–shikimate-conjugated spirocyclic meroterpenoids. Mangiterpene C strongly inhibited the production of NO inducted by LPS (IC50  = 5.97  μ M).